WORKPLACE INCIVILITY AND PERCEIVED ORGANIZATIONAL SUPPORT AS PREDICTORS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG NURSES AT THE UNIVERSITY OF UYO TEACHING HOSPITAL - T. Imbur, Moses; Saaondo, Patrick; Mlumun Mozeh, Christie; S. Ikoroha, Innocent (African Journal of Social and Behavioural Sciences, 2026)
This study examined the influence of workplace incivility and perceived organizational support (POS) on organizational citizenship behaviour (OCB) among nurses at the University of Uyo Teaching Hospital (UUTH). A cross-sectional survey design was adopted, and 120 nurses were randomly selected from different wards and units. Data were collected using standardized measures of workplace incivility, perceived organizational support, and organizational citizenship behaviour. Findings from simple linear regression analysis revealed that workplace incivility had a significant negative effect on organizational citizenship behaviour (β = −.142, t = −1.889, p < .05), accounting for 2% of the variance (R² = .020). Perceived organizational support also had a significant positive influence on organizational citizenship behaviour (β = .295, t = 3.347, p < .01), explaining 8.7% of the variance (R² = .087). Furthermore, multiple regression analysis showed that the joint model was statistically significant (F(2, 117) = 6.25, R = .320, R² = .102, p < .01). However, when both variables were entered simultaneously, only perceived organizational support remained a significant predictor (β = .280, t = 3.124, p < .01), while workplace incivility was not statistically significant (β = −.125, t = −1.658, p = .100). The findings suggest that although workplace incivility significantly reduces organizational citizenship behaviour, perceived organizational support plays a more dominant role in promoting positive discretionary behaviours and may help mitigate the negative effects of incivility. It is recommended that hospital management implement policies that reduce workplace incivility and strengthen support systems to encourage citizenship behaviours that improve healthcare delivery.